Synthesis of rGO supported Cu@FeCo catalyst and catalytic hydrolysis of ammonia borane. Issue 1 (23rd December 2022) - Qiu, Fangyuan; Hao, Xiang; Huang, Wanyou; Wu, Yanling; Chu, Ruixia; Yang, Jun; Fu, Wenjun; Ren, Guohong; Xu, Chuanyan; Bao, Wujisiguleng
Abstract : Highly dispersed Cu@FeCo/rGO catalysts have been prepared by two-step reduction method and used for hydrogen production from ammonia borane (NH3 BH3, AB) hydrolysis at 298 K. Abstract : Highly dispersed Cu@FeCo/rGO catalysts have been prepared by two-step reduction method and used for hydrogen production from ammonia borane (NH3 BH3, AB) hydrolysis at 298 K. The activity and reusability of synthesized composite catalyst were much more higher than Cu@FeCo for AB hydrolysis dehydrogenation at 298 K. Kinetic study manifested that AB hydrolysis dehydrogenation with Cu@FeCo/rGO catalysts was approaching to the first order at different catalyst concentrations. The hydrolysis reaction completed within four minutes, and its maximum hydrogen production rate reached to 7863.0 ml min −1 g −1 at 298 K.